Different migration strategies among Swedish Common Buzzards Buteo buteo revealed by the proportion of white birds - Kjellén, Nils (Ornis Svecica, 1999)
Migrating Common Buzzards Buteo buteo were counted and aged at Falsterbo, Sweden in the autumns of 1990—1996. The study included a total of 48,000 individuals. Among these migrants, birds with a primarily white plumage were separated. Such birds form a significant proportion of the buzzards breeding in Scania, the southernmost Swedish province, but are very rare further north. The proportion of white buzzards at Falsterbo in autumn was also compared with the proportion among birds wintering in Scania. Using white buzzards as indicators of a southern population and comparing them with more normal/dark buzzards breeding further north in Sweden I demonstrate the following differences: (1) The southern population migrates earlier than normal/dark buzzards, adults as well as juveniles. (2) A larger proportion of juveniles than of adults migrates in the southern population. (3) Especially adults in the southern population are resident to a higher degree than more northerly breeders. Such a pattern of leap-frog migration among Swedish Common Buzzards is also supported by ringing recoveries.